Obesity and cancer - Healy, Laura (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Surgery, 2011)
Cancer rates are increasing with predictions of incidence rates doubling between 2000 and 2020. Although several factors are contributory, the rising incidence of overweight and obesity is currently thought to be fuelling cancer rates and has also been linked with pre cancerous lesions. The World Cancer Research Fund (WCRF) now considers that diet and obesity account for 35% of cancer-related deaths, as compared to smoking accounting for 30%. Obesity is an important modifiable risk factor for cancer. At present the strongest support for mechanisms to link obesity and cancer risk involves the metabolic and endocrine effects of obesity and the alterations they induce. This thesis describes several studies of the impact of obesity on different cancers - oesophageal, breast and colorectal cancer - from its' aetiology, factors linked to progression of cancer and treatment outcomes.
Keywords: Surgery, Ph.D.; Ph.D. Trinity College Dublin